Performance Analysis of Cooperative-based Multi-hop Transmission Protocols in Underlay Cognitive Radio with Hardware Impairment - Trung Duy, Tran; Nguyen Quoc Bao, Vo (VNU Journal of Science: Computer Science and Communication Engineering, 2015)
In this paper, we study performances of multi-hop transmission protocols in underlay cognitive radio (CR) networks under impact of transceiver hardware impairment. In the considered protocols, cooperative communication is used to enhance reliability of data transmission at each hop on an established route between a secondary source and a secondary destination. For performance evaluation, we derive exact and asymptotic closed-form expressions of outage probability and average number of time slots over Rayleigh fading channel. Then, computer simulations are performed to verify the derivations. Results present that the cooperative -based multi-hop transmission protocols can obtain better performance and diversity gain, as compared with multi-hop scheme using direct transmission (DT). However, with the same number of hops, these protocols use more time slots than the DT protocol.